2007
DOI: 10.2320/matertrans.mer2006371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing on the Interfacial Structure of Aluminum-Copper Joints

Abstract: The aim of this study is to investigate the structure development and growth kinetics of the interfacial structure of cold roll bonded Al/Cu bimetal sheet. An interfacial structure is developed during the annealing process. The characteristics of the constituent phases at the interface of Al/Cu bimetal are studied by means of scanning electron microscope (SEM), X-ray diffraction (XRD) and transmission electron microscope (TEM). The results indicate that an obvious multi-layers interdiffusion structure is devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 16 publications
(15 reference statements)
5
70
1
1
Order By: Relevance
“…The effects of lattice defects generated by the severe plastic deformation on the diffusion were significantly suppressed by the non-deforming intermetallic layer. However, since the main IMC phase (CuAl 2 ) was of tetragonal structure, including a lot of structural defects, such as grain boundary and dislocations [24], it was unlikely that the effects were completely eliminated in the Cu or Al matrix junction subsequently to the reaction layer becoming continuous. Therefore, it was found that the growth rate of the intermetallic thickness was still more than 14 times greater than the rate acquired from the parabolic growth predictions made with growth rate constant, as obtained from the static heat treatments condition.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…The effects of lattice defects generated by the severe plastic deformation on the diffusion were significantly suppressed by the non-deforming intermetallic layer. However, since the main IMC phase (CuAl 2 ) was of tetragonal structure, including a lot of structural defects, such as grain boundary and dislocations [24], it was unlikely that the effects were completely eliminated in the Cu or Al matrix junction subsequently to the reaction layer becoming continuous. Therefore, it was found that the growth rate of the intermetallic thickness was still more than 14 times greater than the rate acquired from the parabolic growth predictions made with growth rate constant, as obtained from the static heat treatments condition.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…The thickness of the clad sheet interface is approximately 9 µm to 10 µm. Studies have shown that several intermetallic compound (IMC) layers can form with Cu and Al on the contact surface under the effect of thermal diffusion [18][19][20]. The EDS results (Table 2) show that the compositions of the three layers, arranged in a sequence from Al to Cu, correspond to the probable Al 2 Cu, AlCu, and Al 4 Cu 9 phases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study has reported that the refinement of coating grains can improve the hardness of coating [1]. In addition, the formation of intermetallic phases strongly affects the hardness of the sample [9,11].…”
Section: Coating Microhardnessmentioning
confidence: 99%